Gasdermin D Mediates Inflammation-Induced Defects in Reverse Cholesterol Transport and Promotes Atherosclerosis - Opoku, Emmanuel; Traughber, Cynthia Alicia; Zhang, David; Iacano, Amanda J.; Khan, Mariam; Han, Juying; Smith, Jonathan D.; Gulshan, Kailash (Frontiers in Cell and Developmental Biology, 2021)
Activation of inflammasomes, such as Nlrp3 and Aim2, can exacerbate atherosclerosis in mice and humans. Gasdermin D (GsdmD) serves as a final executor of inflammasome activity, by generating membrane pores for the release of mature Interleukin-1beta (IL-1. Inflammation dampens reverse cholesterol transport (RCT) and promotes atherogenesis, while anti-IL-1 antibodies were shown to reduce cardiovascular disease in humans. Though Nlrp3/AIM2 and IL-1 nexus is an emerging atherogenic pathway, the direct role of GsdmD in atherosclerosis is not yet fully clear. Here, we used in-vivo Nlrp3 inflammasome activation to show that the GsdmD-/- mice release ~80% less IL-1 vs WT mice. The GsdmD-/- macrophages were more resistant to Nlrp3 inflammasome mediated reduction in cholesterol efflux, showing ~26% decrease vs. ~60% reduction in WT macrophages. GsdmD expression in macrophages exacerbated foam cell formation in an IL-1 dependent fashion. The GsdmD-/- mice were resistant to Nlrp3 inflammasome mediated defect in RCT, with ~32% reduction in plasma RCT vs. ~ 57% reduction in WT mice, ~ 17% reduction in RCT to liver vs. 42% in WT mice, and ~ 37% decrease in RCT to feces vs. ~ 61% in WT mice. The LDLr anti-sense oligonucleotides (ASO) induced hyperlipidemic mouse model showed the role of GsdmD in promoting atherosclerosis. The GsdmD-/- mice exhibit ~42% decreased atherosclerotic lesion area in females and ~33% decreased lesion area in males vs. WT mice. The atherosclerotic plaque-bearing sections stained positive for the cleaved N-terminal fragment of GsdmD, indicating cleavage of GsdmD in atherosclerotic plaques. Our data show that GsdmD mediates inflammation-induced defect in RCT and promotes atherosclerosis.